Association between dietary inflammatory index and Parkinson’s disease from National Health and Nutrition Examination Survey (2003–2018): a cross-sectional study - Zeng, Zhaohao; Cen, Yanmei; Wang, Lu; Luo, Xiaoguang (Frontiers in Neuroscience, 2023)
Objected To explore the association between Parkinson’s disease (PD) and dietary inflammatory index (DII) scores in adults over 40 years old in the US. Method Data were collected from the National Health and Nutrition Examination Survey (NHANES) conducted from 2003 to 2018. A total of 21,994 participants were included in the study. A weighted univariate and multivariable logistic regression analysis was performed to investigate the association between the DII and PD, in which continuous variables or categorical variables grouped by tertiles was used. The relationship between DII and PD has been further investigated using propensity score matching (PSM) and a subgroup analysis stratified based on DII and PD characteristics. Moreover, restricted cubic spline (RCS) analysis was conducted to examine whether there was a nonlinear association between DII and PD. Results A total of 21,994 participants were obtained for statistical analysis, made up of 263 patients with PD and 21,731 participants without PD. Univariate and multivariable logistics regression analysis showed DII to be positively associated with PD before and after matching. Subgroup analysis revealed a statistical difference in non-Hispanic whites, but RCS analysis suggested that there was no nonlinear relationship between the DII and PD. Conclusion For participants over 40 years of age, higher DII scores were positively correlated with PD. In addition, these results support the ability of diet to be used as an intervention strategy for managing PD.